2009
DOI: 10.1080/02699050902926309
|View full text |Cite
|
Sign up to set email alerts
|

Post-concussion symptoms after traumatic brain injury at 3 and 12 months post-injury: A prospective study

Abstract: PCS symptoms were reported to a greater degree in persons with mild TBI at 3 months post-injury. One year after injury, no differences were found between TBI groups on the presence of PCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 37 publications
12
113
0
Order By: Relevance
“…One possible explanation for the increase in symptoms is that individuals with severe TBI may be less aware of their deficits for organic reasons, and thus these individuals may under-report symptoms during the first months post-injury (40). When the RPQ was added into the regression analysis, it was a significant predictor of HRQL.…”
Section: Discussionmentioning
confidence: 98%
“…One possible explanation for the increase in symptoms is that individuals with severe TBI may be less aware of their deficits for organic reasons, and thus these individuals may under-report symptoms during the first months post-injury (40). When the RPQ was added into the regression analysis, it was a significant predictor of HRQL.…”
Section: Discussionmentioning
confidence: 98%
“…In most patients, cognition recovers and PCS resolve within three months. However, up to 25% of patients (Sigurdardottir et al, 2009) suffer residual PCS, long-term impairment, and sometimes disability (Levin, 2009), so that efficient identification of alterations due to mTBI becomes particularly important. Several cognitive functions are affected by mTBI, including attention (De Monte et al, 2006;Vanderploeg et al, 2005) working memory (Vanderploeg et al, 2005), episodic memory (Tsirka et al, 2011), verbal learning (De Monte et al, 2006;Ruff et al, 1989), and visual memory (Levin et al, 1987;Raskin, 2000;Ruff et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The number and severity of symptoms were collected using the Rivermead Post-Concussion symptoms Questionnaire (RPQ; [60][61][62]), as in previous studies [11,14,21,39,40,53,63]. PCS was diagnosed if participants reported that three (or more) of the symptom categories listed in the ICD-10 criteria were more of a problem after the head injury.…”
Section: Diagnosismentioning
confidence: 99%